PENGARUH PROFITABILITAS, DER, KOMISARIS INDEPENDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Yohannes, Silaban Ferdiansyah; Zirman, Zirman; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to empirically examine and analyze the effect of profitability, der, independent commissioners and institutional ownership on tax avoidance. The population of this study were all companies in the consumer goods industry listed on the Indonesia Stock Exchange in 2016-2018. The sample of this research is the consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2016-2018 that meet criteria such as having audited financial reports, not experiencing losses in the study period and having independent commissioners. The data used are secondary data obtained from the Indonesia Stock Exchange with a total sample of 87 financial reports. The data analysis method used the classical assumption test, partial test, descriptive statistical test and multiple regression analysis. The results showed that der had an effect on tax avoidance. Meanwhile, profitability, independent commissioners and institutional ownership had no effect on tax avoidance.Keyword : Profitability, DER, Independent Commissioner, Institutional Ownership, Tax Avoidance